Tissue trauma induced by lens fragmentation patterns in femtosecond laser assisted cataract surgery - Leonardo Mastropasqua; Toto Lisa; Peter Mattei; Luca Vecchiarino; Alessandra Mastropasqua; Gennaro Falconio; Marzio Guido Di (Journal of Applied Robotics and Artificial Intelligence, 2017)
Background: To evaluate cumulative dissipated energy (CDE), laser time, central corneal thickness and endothelial cell loss after two different fragmentation pattern by means of femtosecond laser-assisted cataract surgery (FLACS). Methods: Eighty eyes of 80 patients that underwent FLACS were randomized in two groups: mixed chop and dice lens fragmentation pattern (group 1 with 40 eyes) and mixed chop and cylindrical lens fragmentation pattern (group 2 with 40 eyes). Results: Cumulative dissipated energy was significantly lower in group 1 compared to group 2 (p<0.001). Postoperatively there was a decrement of endothelial cells count at the centre of the cornea in both groups compared with preoperative values with greater decrease in Group 2 (p<0.001). The thickness at the tunnel site showed a greater increase in group 2 compared to group 1 immediately after surgery (p<0.001) The thickness measured at the center of the cornea increased slightly immediately after surgery and showed a similar decrease in both groups. The increase was greater in Group 2 (p<0.001). Conclusions: Both lens fragmentation patterns were effective in nucleus disassembly. Nevertheless dice pattern was related with a lower amount of CDE and induced lower central endothelial cell loss and lower increase of corneal thickness.
Keywords: femtosecond laser-assisted cataract surgery